Factors Associated With Pediatrician Responses to Alternative Immunization Schedule Requests. (February 2018) - Mohanty, Salini; Feemster, Kristen A.; Buttenheim, Alison; Moser, Charlotte A.; Field, Robert I.; Mayer, Whitney; Carroll-Scott, Amy
We conducted a cross-sectional online survey among 4 chapters of the American Academy of Pediatrics from July through October 2014 to describe characteristics of pediatricians and practices associated with practice-level responses to alternative immunization schedule requests. Among 374 pediatricians, 58% reported frequent alternative immunization schedule requests and 24% reported feeling comfortable using them. Pediatricians who work in practices that accommodate alternative immunization schedule requests have increased odds of having a high frequency of alternative immunization schedule requests, and beliefs that relationships with families would be negatively affected if they refused requests. Practices that discontinue care to families who request alternative immunization schedules have increased odds of being a private group practice and having a formal office vaccine policy. Pediatricians are frequently asked to use alternative immunization schedules and many are not comfortable using them. Practice-level responses to alternative immunization schedules are associated with characteristics of pediatricians and practices.